2021
DOI: 10.1111/jam.15100
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced removal of Congo red dye from aqueous solution by surface modified activated carbon with bacteria

Abstract: Aims:The adsorption behaviour and mechanisms of the surface modified activated carbon with bacteria was evaluated. Methods and Results: 16S rRNA was employed to identify the hydrocarbondegrading bacteria. The bacteria was characterized by TEM and electron microscope. The surface modified activated carbon with bacteria was characterized by SEM. The adsorption behaviour was tested by static adsorption and dynamic adsorption. Conclusion:The adsorption efficiency of the modified activated carbon was high when pH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…This suggests that the decolorization of CR by JAS1 effectuates an adsorption phenomenon in addition to its enzymatic degradation. Many studies have previously reported CR decolorization by microbes following its surface adsorption [7,36,[55][56][57]. Moreover, many studies report the specific use of CR to identify Agrobacterium isolates that produce curdlan (an EPS) because of its affinity with these sugars [58,59].…”
Section: Congo Red Adsorbs To the Jas1 Surfacementioning
confidence: 99%
“…This suggests that the decolorization of CR by JAS1 effectuates an adsorption phenomenon in addition to its enzymatic degradation. Many studies have previously reported CR decolorization by microbes following its surface adsorption [7,36,[55][56][57]. Moreover, many studies report the specific use of CR to identify Agrobacterium isolates that produce curdlan (an EPS) because of its affinity with these sugars [58,59].…”
Section: Congo Red Adsorbs To the Jas1 Surfacementioning
confidence: 99%
“…All adsorption experiments were conducted using 50-mL glass tubes in accordance with our previous work (Wang et al, 2021;Pi et al, 2022). To investigate the adsorption isotherm equilibrium, 50.0 mL of a NOR/LEV solution was mixed with 5 mg Fe 3 O 4 or a magnetic microrobot, with initial NOR/LEV concentrations ranging from 10 to 50 mg/L.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Among them, the adsorption method has the advantages of low cost, safety, simplicity, and easy recovery. In recent years, the adsorption method has been applied to the removal of dyes and antibiotics in wastewater and has achieved excellent results. , Many traditional materials have been used in adsorption to treat industrial dye wastewater, such as biomaterials, activated carbon, metal oxides, layered dihydroxides, montmorillonite, kaolinite, cellulose, chitosan (CS), zeolite, graphene oxide (GO), calcium alginate, etc. These traditional adsorbents have the limitations of low adsorption performance, complex preparation, and high cost.…”
Section: Introductionmentioning
confidence: 99%